Hexagynephilippiana gen. et sp. nov., a piperalean angiosperm from the Early Cretaceous of northern Gondwana (Crato Formation, Brazil). Issue 6 (1st December 2014) - Coiffard, Clément; Mohr, Barbara A.R.; Bernardes-de-Oliveira, Mary E.C.
Abstract: Hexagyne philippiana gen. et sp. nov. represents the first macrofossil piperalean taxon from the Early Cretaceous (Aptian). The fossil material from northern Gondwana consists of a twig with well‐preserved leaves and a characteristic venation pattern plus a twig with attached leaves and several flowers combined in a raceme. The new taxon shares many characters, such as leaf shape and venation pattern, as well as flower morphology, including a clearly developed perianth and six fused carpels, with extant Aristolochiaceae (sensu lato) and/or related clades. Representatives of Aristolochiaceae grow today in Laurasia. The Early Cretaceous finds in South America (Brazil) may indicate a Gondwanan origin of this group. Based on its morphology, Hexagyne gen. nov. might have had an ecology of an understory plant in a shaded environment.